Pengaruh Kesadaran Halal Dan Gaya Hidup Terhadap Keputusan Pembelian Konsumen Muslim Pada Restoran Jepang Di Jakarta - Nurfajrina, Alifah; Handayani, Tati; Sari, Lili Puspita (Universitas Siliwangi, 2021)
This study aims to determine and analyze the factors of halal awareness and lifestyle on the purchasing decisions of Muslim consumers at Japanese restaurants in Jakarta using a quantitative approach. The population selected in this study were Muslim consumers who had visited a Japanese restaurant located in the Jakarta area. For the number of samples in this study using as many as 150 Muslim consumers of Japanese restaurants in the Jakarta area. The sampling instrument in this study was obtained from distributing questionnaires. The analytical technique used to determine the magnitude of the effect is multiple linear regression. The data processing tool used for data analysis in this research is SPSS software version 20. The results of the tests carried out show that the variables of halal awareness and lifestyle partially and simultaneously have a significant effect on purchasing decisions of Muslim consumers at Japanese restaurants in Jakarta.